Learning Engagement and Its Influencing Factors Among High School Students in Economically Developed Areas in China - HOU, Yongmei; Yingxin, Cen (Advances in Social Sciences Research Journal, 2021)
Objective: To explore the characteristics and its relevant factors of learning engagement among high school students in economically developed areas in China. Methods: 808 high school students in Guangdong Province were selected by stratified cluster sampling. They were investigated with Utrecht Work Engagement Scale-Student-Chinese Version (UWES-S-CV), Academic Self-Efficacy Scale (ASES), Interpersonal Comprehensive Diagnostic Scale (ICDS), Short-Form Egna Minnen AV Barndoms Uppprostran (s-EMBU), Emotional Support Questionnaire for Middle School Students to Understand Teachers (ESQUT) and a self-compiled general personal information questionnaire. Results: ⑴ The total score of UWES-S-CV, ASES, ICDS and the scores of three dimensions in UWES-S-CV, two subscales of ASES and four dimensions of ICDS, as well as the mother overprotection of s-EMBU were at the medium level. The total score of ESQUT and its four dimensions were at the medium high level. The scores of father’s and mother’s warmth of s-EMBU were at the high level, while the score of father’ negation, mother's negation and father's overprotection were at the low level. ⑵ Multivariate stepwise linear regression analysis showed that 12 factors such as student origin, school category, class category, learning interest, the teaching method used most commonly, mother's education level, learning behavior self-efficacy, learning ability self-efficacy, father's warmth, mother's warmth, care and encouragement were positively correlated with the total score of UWES-S-CV (β=.120~.433, all P<.01), while grade, family economic status, self-rated learning burden, communication and making friends, father’s negation and mother’s negation were negatively correlated with the total score of UWES-S-CV (β=-. 073~ -. 407, all P <. 05). Conclusion The learning engagement among high school students needs to be improved. Social environment, family rearing style, school education and teaching style, as well as individual factors may be the main influencing factors of high school students' learning engagement.